A STUDY ON ANALYSIS OF MARKETING STRATEGIES FOR TRIBAL PRODUCTS IN JAWADHU HILLS, TIRUVANNAMALAI DISTRICT - Vadivel, P.; Palanisamy, A.; D.Sathiyamoorthy; Anand, S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Numerous tribal people inhabit the Jawadhu Hills region in Tamil Nadu's Tiruvannamalai district, where they create a variety of distinctive goods such traditional handicrafts, herbal medicines, handcrafted fabrics, and organic agricultural products. Notwithstanding the distinctiveness and superior quality of these goods, marketing and expanding their consumer bases present major obstacles for the native people. The purpose of this study is to evaluate current marketing tactics for Jawadhu Hills tribal products and to pinpoint possible areas for development. Through surveys and interviews, information was gathered from 200 respondents—including urban consumers and tribal producers—using a mixed-methods approach that combined qualitative and quantitative research. The data was analyzed using statistical methods such the chi-square test, t-test, F-test, regression analysis, correlation analysis, ANOVA, and simple percentage analysis. According to the report, tribal producers encounter obstacles such restricted access to digital marketing platforms, poor infrastructure, and a lack of marketing expertise, despite the rising demand for sustainable and organic products. The report makes recommendations based on these results, including integrating digital marketing, enhancing branding, creating better distribution channels, and emphasizing sustainable pricing techniques. The findings offer insightful information about how to better promote tribal items to increase their exposure and market reach, which would eventually improve the economic standing of the tribal people while conserving their cultural legacy.